Switching-Off Adora2b in Vascular Smooth Muscle Cells Halts the Development of Pulmonary Hypertension - Mertens, Tinne C. J.; Hanmandlu, Ankit; Tu, Ly; Phan, Carole; Collum, Scott D.; Chen, Ning-Yuan; Weng, Tingting; Davies, Jonathan; Liu, Chen; Eltzschig, Holger K.; Jyothula, Soma S. K.; Rajagopal, Keshava; et al. (Frontiers in Physiology, 2018)
Background: Pulmonary hypertension (PH) is a devastating and progressive disease characterized by excessive proliferation of pulmonary artery smooth muscle cells (PASMCs) and remodeling of the lung vasculature. Adenosine signaling through the ADORA2B receptor has previously been implicated in disease progression and tissue remodeling in chronic lung disease. In experimental models of PH associated with chronic lung injury, pharmacological or genetic inhibition of ADORA2B improved markers of chronic lung injury and hallmarks of PH. However, the contribution of ADORA2B expression in the PASMC was not fully evaluated. Hypothesis: We hypothesized that adenosine signaling through the ADORA2B receptor in PASMC mediates the development of PH. Methods: PASMCs from controls and patients with idiopathic pulmonary arterial hypertension (iPAH) were characterized for expression levels of all adenosine receptors. Next, we evaluated the development of PH in ADORA2Bf/f-Transgelin (Tagln)cre mice. These mice or adequate controls were exposed to a combination of SUGEN (SU5416, 20mg/kg/b.w. IP) and hypoxia (10% O2) for 28 days (HX-SU) or to chronic low doses of bleomycin (BLM, 0.035U/ kg/b.w. IP). Cardiovascular readouts including right ventricle systolic pressures (RVSPs), Fulton indices and vascular remodeling were determined. Using PASMCs we identified ADORA2B-dependent mediators involved in vascular remodeling. These mediators: IL-6, hyaluronan synthase 2 (HAS2) and tissue transglutaminase (Tgm2) were determined by RT-PCR and validated in our HX-SU and BLM models. Results: Increased levels of ADORA2B were observed in PASMC from iPAH patients. ADORA2Bf/f-Taglncre mice were protected from the development of PH following HX-SU or BLM exposure. In the BLM model of PH, ADORA2Bf/f- Taglncre mice were not protected from the development of fibrosis. Increased expression of IL-6, HAS2 and Tgm2 was observed in PASMC in an ADORA2B-dependent manner. These mediators were also reduced in ADORA2Bf/f- Taglncre mice exposed to HX-SU or BLM. Conclusions: Our studies revealed ADORA2B-dependent increased levels of IL-6, hyaluronan and Tgm2 in PASMC, consistent with reduced levels in ADORA2Bf/f- Taglncre mice exposed to HX-SU or BLM. Taken together, our data indicates that ADORA2B on PASMC mediates the development of PH through the induction of IL-6, hyaluronan and Tgm2. These studies point at ADORA2B as a therapeutic target to treat PH.